Model PBL Scaffolding Untuk Meningkatkan Aktivitas Metakognisi Siswa Slow Learner - Nopem Kusumaningtyas Sumitro; Era Dewi Kartika; Lailatul Mubarokah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Slow learner students often face difficulties in metacognitive activities such as awareness, evaluation, and regulation when solving mathematical problems, which leads to low problem-solving achievement. This study aims to develop and test the validity, practicality, and effectiveness of a Problem Based Learning model integrated with Level 2 scaffolding, called PBL Scaffolding, to enhance metacognitive activities of slow learners in junior high school mathematics. The research employed the Borg & Gall R&D method through nine stages, from preliminary study to limited field testing. The model and learning tools were validated by two experts in mathematics education and educational psychology, tested for practicality through observation of teacher implementation and student-teacher questionnaires, and evaluated for effectiveness using pretest-posttest design on 20 slow learner students. Data were analyzed descriptively using content validity ratio, percentage, and normalized N-Gain. The results indicated that the PBL Scaffolding model achieved a mean validity score of 3.57 or 89.06% in the very valid category. The model was very practical with syntax implementation of 84.38% and student-teacher response rates of 86.45% and 88.20%. Effectiveness testing showed an average N-Gain of 0.55 in the medium category, with the highest improvement in the evaluation indicator at 0.60. It is concluded that PBL Scaffolding is valid, practical, and effective for improving metacognitive activities of slow learners because each PBL phase is paired with structured scaffolding prompts that guide students’ thinking processes.